Implementasi Supervisi Peer To Peer dalam Mengembangkan Kompetensi Guru - Supatah, Supatah; Thohri, Muhammad; Fitriani, Moh. Iwan; Safinah, Safinah (Jurnal Manajemen & Budaya, 2024)
This research aims to describe the implementation of peer to peer supervision in developing teacher competency at SMPN 17 Mataram and MTSN 3 Mataram, Sekarbela sub-district. This research uses qualitative research methods to produce descriptive data. The data in this research consists of two types, namely; primary data and secondary data. Data collection techniques use; 1) Observation 2) Interview 3) Documentation. The data analysis techniques that researchers use are; Data collection coincides with the research process, presenting data, reducing data and drawing conclusions. The techniques used to test the validity of the data are; source triangulation and time triangulation. The research results show that the implementation of peer to peer supervision at SMPN 17 Mataram and MTSN 3 Mataram involves various forms, such as determining teaching administration and assessing learning tools. Teacher competencies developed through peer supervision include collaboration skills, communication, pedagogical knowledge, and the use of technology at SMPN 17 Mataram, as well as self-reflection skills, collaboration, active learning skills, and pedagogical knowledge at MTSN 3 Mataram